DAKWAH FARDIYAH MELALUI PERNIKAHAN SECARA ISLAM PADA MASYARAKAT SAMIN (SEDULUR SIKEP) DI DUSUN BOMBONG DESA BATUREJO KECAMATAN SUKOLILO KABUPATEN PATI - Trianingsih, Zulfi; Qibtiyah, Maryatul; Umriana, Anila (Jurnal Ilmu Dakwah, 2017)
This study is a qualitative research that aims to describe and explain the customary marriage of the Islamic Society of Samin and the analysis of da'wah fardiyah to the Islamic marriage of Samin (Sedulur Sikep) community in Bombong Village Baturejo Village Sukolilo District Pati Regency. This type of research is a qualitative research. The source of research data is the marriage perpetrators of Islam between the Samin community and Muslims, the head of the Office of Religious Affairs (KUA) and the wife of one of the Samin community elders. Methods of data collection using interviews, observation, and documentation. Methods of data analysis using Miles and Huberman model, including data reduction, display data, conclusion. The results showed that Islamic marriage Samin society consists of several stages of application, pengislaman / shahada, marriage ceremony and prayer. Da'wah fardiyah on the Samin community has a tendency of the Islamic party to be da'i in his family which is shown by his advice in daily activities to carry out the command of Allah in accordance with Islamic Shari'a.